Endogenous institutions and economic growth: evidence from China - Li, Zhao; Chu, Yujing (Instytucje endogeniczne a wzrost gospodarczy na przykładzie Chin, 2020)
The paper examined how economic institutions affect capital accumulation in the private firms sector through the finance sector and the operation objectives of different ownership firms in a socialist market economy with Chinese characteristics, which extended the neo-classical economic growth method. The Author found that economic institutions were the main factors affecting the efficiency of capital allocation between the private sector and the state-owned sector. Compared with the state-owned sector, economic institutions lead private sector to a decrease in loans and government subsidies through finance sector, and to an increase in its production costs. The evidence suggests that private firms make efforts to hire special human capital to improve economic institutions as a substitute for political capital. Considering that the strategy of China’s economic institutions reform was a national promotion which followed after a regional pilot, this paper found that the economic institutions’ reform pilot areas had a more significant impact on economic growth
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 1, s. 54-77
Keywords: economic growth; economic institutions; ownership discrimination; capital allocation; instytucje gospodarcze; dyskryminacja własności; alokacja kapitału; wzrost gospodarczy